2018
DOI: 10.1029/2018sw001881
|View full text |Cite
|
Sign up to set email alerts
|

O+Escape During the Extreme Space Weather Event of 4–10 September 2017

Abstract: We have investigated the consequences of extreme space weather on ion outflow from the polar ionosphere by analyzing the solar storm that occurred early September 2017, causing a severe geomagnetic storm. Several X‐flares and coronal mass ejections were observed between 4 and 10 September. The first shock—likely associated with a coronal mass ejection—hit the Earth late on 6 September, produced a storm sudden commencement, and began the initial phase of the storm. It was followed by a second shock, approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…The average total O + velocity v and magnetic field strength B pm in the plasma mantle (−5 < X G S M <−2R E ) is 120 km/s and 50 nT during the strongest geomagnetic conditions. Schillings et al () observed a convection speed v ⊥pc in the polar cap of 20.6 km/s (at an altitude of 6.5 R E and magnetic field strength B pc of 145 nT) during a strong geomagnetic storm associated with the extreme space weather event in September 2017. This convection speed can be scaled to the considered plasma mantle as vpm=vpcBpcfalse/Bpm=35 km/s.…”
Section: Discussionmentioning
confidence: 99%
“…The average total O + velocity v and magnetic field strength B pm in the plasma mantle (−5 < X G S M <−2R E ) is 120 km/s and 50 nT during the strongest geomagnetic conditions. Schillings et al () observed a convection speed v ⊥pc in the polar cap of 20.6 km/s (at an altitude of 6.5 R E and magnetic field strength B pc of 145 nT) during a strong geomagnetic storm associated with the extreme space weather event in September 2017. This convection speed can be scaled to the considered plasma mantle as vpm=vpcBpcfalse/Bpm=35 km/s.…”
Section: Discussionmentioning
confidence: 99%
“…The timing for individual events discussed in subsections 3.1–3.5 are marked between panels (d) and (e). The Cluster traversal of the cusp and polar cap (Schillings et al, ) is also marked. SEM = Space Environmental Monitor; IMF = interplanetary magnetic field.…”
Section: Datamentioning
confidence: 99%
“…For this examination, we took a 30‐min running average of N e ·V i at 400 km altitude from the Svalbard 42 m antenna between 08:30 and 11:00 UT (about 10–12 LT), because the outflow is maximized at this local time for this latitude according to the past statistics (e.g., Moore et al, , and references therein). The simultaneous Cluster observation of the same event at high altitudes in the prenoon region shows that the ICME arrivals caused an increase of ionospheric ion outflow (Schillings et al, ). Therefore, the increased solar irradiation most likely contributed to preconditions for enhancement of the ion outflow.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations